Cardiac dysfunction in sucrose-fed rats is associated with alterations of phospholamban phosphorylation and TNF-α levels - Gregolin, Cristina Schmitt [UNESP]; do Nascimento, Milena; de Souza, Sérgio Luiz Borges; Mota, Gustavo Augusto Ferreira [UNESP]; Luvizotto, Renata de Azevedo Melo; Sugizaki, Mário Mateus; Bazan, Silméia Garcia Zanati [UNESP]; de Campos, Dijon Henrique Salomé [UNESP]; Camacho, Camila Renata Corrêa [UNESP]; Cicogna, Antonio Carlos [UNESP]; do Nascimento, André Ferreira (Elsevier, 2024)
Introduction: High sucrose intake is linked to cardiovascular disease, a major global cause of mortality worldwide. Calcium mishandling and inflammation play crucial roles in cardiac disease pathophysiology. Objective: Evaluate if sucrose-induced obesity is related to deterioration of myocardial function due to alterations in the calcium-handling proteins in association with proinflammatory cytokines. Methods: Wistar rats were divided into control and sucrose groups. Over eight weeks, Sucrose group received 30% sucrose water. Cardiac function was determined in vivo using echocardiography and in vitro using papillary muscle assay. Western blotting was used to detect calcium handling protein; ELISA assay was used to assess TNF-α and IL-6 levels. Results: Sucrose led to cardiac dysfunction. RYR2, SERCA2, NCX, pPBL Ser16 and L-type calcium channels were unchanged. However, pPBL-Thr17, and TNF-α levels were elevated in the S group. Conclusion: Sucrose induced cardiac dysfunction and decreased myocardial contractility in association with altered pPBL-Thr17 and elevated cardiac pro-inflammatory TNF-α.
Keywords: Calcium handling; Cardiac function; Diet-induced obesity; Sucrose